2020
DOI: 10.1002/eji.202048745
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells are crucial for humoral immunity establishment by SA14‐14‐2 live attenuated Japanese encephalitis vaccine in mice

Abstract: The live attenuated SA14‐14‐2 Japanese encephalitis (JE) vaccine is a historical vaccine that protects against JE. Despite its extensive use, the mechanism of protective immunity conferred by the SA14‐14‐2 vaccine is not well established. Here, we used mouse models to understand the mechanism of the development of humoral immunity against the vaccine. The vaccine induces robust GC responses within a week postimmunization. In lethal virus challenge, we show that CD4+ T cells alone, but not CD8+ T cells, are suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…In this study, immunization of the attenuated vaccine enhanced the CD4 + T cell responses significantly (Figure 2C), which may explain the high titer of neutralizing antibodies detected in the SA14-14-2 group. This finding is consistent with a previous study which reported that the CD4 + T cells stimulated by the SA14-14-2-attenuated vaccine are sufficient to give complete protection to mice, depending on the antibody response [35]. It has been well known that an mRNA vaccine could stimulate both CD4 + and CD8 + T cell responses [36].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, immunization of the attenuated vaccine enhanced the CD4 + T cell responses significantly (Figure 2C), which may explain the high titer of neutralizing antibodies detected in the SA14-14-2 group. This finding is consistent with a previous study which reported that the CD4 + T cells stimulated by the SA14-14-2-attenuated vaccine are sufficient to give complete protection to mice, depending on the antibody response [35]. It has been well known that an mRNA vaccine could stimulate both CD4 + and CD8 + T cell responses [36].…”
Section: Discussionsupporting
confidence: 92%
“…Although NK- and CD8 + T-cells are most often associated with the cytolytic response to respiratory infection, previous studies suggest that they are also important for vaccine-induced antibody responses to antigens from influenza ( Herrero-Fernández et al, 2019 ; Picard et al, 2022 ) and other pathogens ( Kalia et al, 2021 ). Given this, we sought to determine whether cell-specific granzyme expression was associated with hemagglutination inhibition (HAI) antibody titres prior to and following seasonal high-dose vaccination in our older adult participants.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CD8+ is essential for clearance of WNV and in the CNS and recovery in mouse models [ 162 ], and variation in susceptibility was observed in mice deficient in Fas- or perforin-dependent cytolytic pathways between WNV lineage I and II, JEV and MVEV [ 161 ], which highlights the importance of elucidating a T cell response for specific flaviviruses of the same antigenic complex. Recent studies highlighted the important role of CD8+ cells in eliciting antibody-mediated protection in response to JEV vaccination in mice and in protecting JEV-infected mice via granule-mediated cytotoxic effects with a contribution of γ/δ TCR expressing T cells [ 163 , 164 ]. The T cell immune response in MVEV and USUV infections is less thoroughly defined.…”
Section: Je Serocomplex Flavivirus Immune Responsementioning
confidence: 99%